Design and Implementation of a Hybrid Single T-Type Double H-Bridge Multilevel Inverter (STDH-MLI) Topology - Rawa, Muhyaddin; Siddique, Marif Daula; Mekhilef, Saad; Shah, Noraisyah Mohamed; Bassi, Hussain; Seyedmahmoudian, Mehdi; Horan, Ben; Stojcevski, Alex (MDPI, 2019)
Multilevel inverters are proficient in achieving a high-quality staircase output voltage waveform with a lower amount of harmonic content. In this paper, a new hybrid multilevel inverter topology based on the T-type and H-bridge module is presented. The proposed topology aims to achieve a higher number of levels utilizing a lower number of switches, direct current (dc) voltage sources, and voltage stresses across different switches. The basic unit of the proposed single T-type and double H-bridge multilevel inverter (STDH-MLI) produces 15 levels at the output using three dc voltage sources. The proposed topology can be extended by connecting a larger number of dc voltage sources in the T-type section. The nearest level control (NLC) switching technique is used to generate gate pulses for switches to achieve a high-quality output voltage waveform. In addition, a simplified way to achieve NLC is also described in the paper. A detailed comparison with other similar topologies is provided to set the benchmark of the proposed topology. Finally, experimental work is carried out to validate the performance of the proposed topology. © 2019 by the authors